Accessibility in designing centralised warehousing: Case of health care logistics in Northern Finland. (July 2017) - Kotavaara, Ossi; Pohjosenperä, Timo; Juga, Jari; Rusanen, Jarmo
Abstract: Long distances and sparse service networks set challenging conditions for material logistics in health care. Globally, health care organisations have been making structural changes towards centralised warehousing and deliveries. In Northern Finland, material logistics of the public health care system rely mainly on numerous separate order and delivery systems, although logistics needs, ordering and stock in different health care facilities correspond to each other. As centralised logistics in orders and deliveries may lead to remarkable savings, pressure for centralised management is high. This paper analyses how effectively a potential centralised warehousing system can be organised based on its spatial components. These include optimal location of one or more warehouses, delivery network coverage and efficiency of routes, as well as accessibility of health centres and hospitals. The geographic information systems (GIS) -based accessibility analytical framework described in this study applies vehicle routing and heuristic computations to location-allocation of warehouses to potential sites by optimising transport cost with a constraint to provide service to at least 90% of delivery demand. The spatial data include the road network, health care facility locations with rough estimates of freight demand nodes and potential locations of warehouse facilities. The main findings of the study show that majority of health centres and hospitals can be effectively reached by a delivery network based on one or two warehouses. Furthermore, the efficiency of the delivery network does not increase remarkably by increasing the number of warehouses, when measured as driving time. Highlights: Optimised delivery routes can be applied to solve the warehouse location problem. Increasing the number of warehouses has a minimal effect on delivery efficiency. Majority of sparse health care freight can be served by centralised warehouses. Trade-off between service level and costs excludes the most distant demand. For most sparse units frugal solutions with other transports could be beneficial.